Machine Translation - Kumar, Ashok (DESIDOC Journal of Library & Information Technology, 2002)
Machine translation (MT) is an important technology which assumes significance in view of increasing globalisation and sharing of information among all the countries. The article attempts to bring the status and various features of MT to the notice of providers and users of information. MT has moved from mainframes to personal computer and is thus available to all for personal and organisational use. The paper describes various types of MT systems and the processes involved in translation. It also gives a brief idea of development of MT systems and the software available. http://dx.doi.org/10.14429/dbit.14.6.3109